2017
DOI: 10.1080/13543784.2017.1302428
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein antagonists in early stage clinical trials for NSCLC

Abstract: Cancer cells have a higher need of chaperones than normal cells to prevent the toxic effects of intracellular protein misfolding and aggregation. Heat shock proteins (Hsps) belong to these chaperones; they are classified into families according to molecular size. Hsps are upregulated in many cancers and inhibition can inhibit tumor growth by destabilizing proteins necessary for tumor survival. In non-small cell lung cancer (NSCLC), there are three different Hsp antagonist classes that are in (early) clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 63 publications
(66 reference statements)
2
44
0
Order By: Relevance
“…We noted that the AEs with TAS-116 were similar to those reported with previous clinical studies of HSP90 inhibitors: gastrointestinal disorders, hepatic enzyme increased, and eye disorders such as night blindness and blurred vison (12,13,17,18).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We noted that the AEs with TAS-116 were similar to those reported with previous clinical studies of HSP90 inhibitors: gastrointestinal disorders, hepatic enzyme increased, and eye disorders such as night blindness and blurred vison (12,13,17,18).…”
Section: Discussionsupporting
confidence: 83%
“…HSP90 has been regarded as one of targets for cancer treatment, as HSP90 inhibition may block multiple signaling pathways in tumor cells, resulting in potent, selective anticancer activity (1,3,5). Although many HSP90 inhibitors including ansamycine-, purine-, and resorcinol derivatives have been developed, none of them have been approved for any cancer indication due to their limited single-agent clinical activity and off-target and/or HSPrelated toxicities, such as eye disorders (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…In fact inhibitors of several HSPs are under clinical trials (see e.g. [108]). We found that one FDA approved drug Gilotrif, which is a client of HSP90, together with a HSP90 inhibitor showed much better anti-cancer effects than using Gilotrif alone in in vivo animal study (see Table 1).…”
Section: Targeting Hsp90 Alonementioning
confidence: 99%
“…2c ), indicating the effectiveness of NCT-50 in suppressing the tumorigenicity of NSCLC cells, regardless of their drug resistance status. NCT-50 displayed weak but comparable cytotoxic effects in NSCLC cells compared with known Hsp90 inhibitors that have been evaluated in clinical trials such as ganetespib and PU-H71 31 , 32 (Fig. 2d ).…”
Section: Resultsmentioning
confidence: 92%